Influence of preventive dental treatment on mutans streptococci counts in patients undergoing head and neck radiotherapy - Meca, Lívia Buzati; Souza, Fátima Regina Nunes de; Tanimoto, Helio Massaioshi; Castro, Alvimar Lima de [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (FapUNIFESP (SciELO), 2009)
The aim of this study was to evaluate the influence of chlorhexidine gluconate, sodium fluoride and sodium iodine on mutans streptococci counts in saliva of irradiated patients. Forty-five patients were separated into three experimental groups and received chlorhexidine (0.12%), sodium fluoride (0.5%) or sodium iodine (2%), which were used daily during radiotherapy and for 6 months after the conclusion of the treatment. In addition, a fourth group, composed by 15 additional oncologic patients, who did not receive the mouthwash or initial dental treatment, constituted the control group. Clinical evaluations were performed in the first visit to dental clinic, after initial dental treatment, immediately before radiotherapy, after radiotherapy and 30, 60, 90 days and 6 months after the conclusion of radiotherapy. After clinical examinations, samples of saliva were inoculated on SB20 selective agar and incubated under anaerobiosis, at 37oC for 48 h. Total mutans streptococci counts were also evaluated by using real-time PCR, through TaqMan system, with specific primers and probes for S. mutans and S. sobrinus. All preventive protocols were able to reduce significantly mutans streptococci counts, but chlorhexidine gluconate was the most effective, and induced a significant amelioration of radiotherapy side effects, such as mucositis and candidosis. These results highlights the importance of the initial dental treatment for patients who will be subjected to radiotherapy for head and neck cancer treatment.
Keywords: anticaries agent; chlorhexidine; chlorhexidine gluconate; drug derivative; fluoride sodium; sodium iodide; topical antiinfective agent; adult; bacterial count; clinical trial; controlled clinical trial; controlled study; dental caries; drug effect; female; head and neck tumor; human; isolation and purification; longitudinal study; male; microbiology; middle aged; mouth hygiene; nonparametric test; polymerase chain reaction; radiotherapy; randomized controlled trial; saliva; standard; Streptococcus mutans; time; Adult; Anti-Infective Agents, Local; Cariostatic Agents; Chlorhexidine; Colony Count, Microbial; Dental Caries; Female; Head and Neck Neoplasms; Humans; Longitudinal Studies; Male; Middle Aged; Oral Hygiene; Polymerase Chain Reaction; Radiotherapy; Saliva; Sodium Fluoride; Sodium Iodide; Statistics, Nonparametric; Time Factors; Young Adult